Improved manufacturability of ZrO2 MIM capacitors by process stabilizing HfO2 addition - Mueller, J.; Boescke, T. S.; Schroeder, U.; Reinicke, M.; Oberbeck, L.; Zhou, Dayu; Weinreich, W.; Kuecher, P.; Lemberger, M.; Frey, Lothar (Microelectronic Engineering, 2009)
A broad compositional range of the dielectric material Zr1-xHfxO2 was evaluated with respect to its applicability in DRAM storage capacitors. The paper reports on phase composition, crystallization behavior, and electrical properties of the mixed system in planar metal-insulator-metal (MIM) capacitors. Admixture of HfO2 into ZrO2 proved to stabilize the deposition process at high temperatures without degrading the dielectric properties of the film. Compared to pure ZrO2 the 30–40% HfO2 containing films showed improved scalability (capacitance equivalent thickness 0.73 nm at 8 * 10-9 A/cm2) as well as improved reliability.
Keywords: ALD; Capacitor; Dielectric; DRAM; Hafnium; Hafnium zirconate; High-k; Metal-insulator-metal; MIM; Reliability; Zirconium